ANXIETY, DEPRESSION, AND QUALITY OF LIFE OF NURSES WORKING IN PUBLIC HOSPITALS - Sant’Anna Aragão, Felipe Matheus (2024)
Nursing is often described as the art of caring, providing holistic patient assistance without time restrictions. However, due to this nature of work, it is common for these professionals to present symptoms of mental illnesses such as anxiety and depression. This results in a reduction in the quality of life at work, directly affecting the efficiency of care provision. This study aimed to verify the presence of anxiety and depression symptoms, as well as the index of quality of life at work among nurses working in the inpatient sector of public hospitals in the city of Aracaju. Among the 128 professionals included in the sample, 46.1% presented anxiety symptoms and 30.5% depression symptoms, according to the HADS scale. Additionally, 66.4% of nurses reported an unsatisfactory quality of life at work index (QLWI). The majority of professionals who presented symptoms of both diseases were female; 17.2% had two employment bonds, and 19.5% reported an unsatisfactory QLWI. Therefore, it is possible to infer that the accumulation of employment bonds and the reduction in quality of life at work may have been determining factors for the development of these symptoms. It is concluded that it is extremely important to improve working conditions, safety, and remuneration, as well as increase the institutional appreciation and recognition of nursing professionals. This would contribute to raising the quality of life indices at work and reducing the need for multiple employment bonds.